2020
DOI: 10.3389/fnins.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

Vigilance Effects in Resting-State fMRI

Abstract: Measures of resting-state functional magnetic resonance imaging (rsfMRI) activity have been shown to be sensitive to cognitive function and disease state. However, there is growing evidence that variations in vigilance can lead to pronounced and spatially widespread differences in resting-state brain activity. Unless properly accounted for, differences in vigilance can give rise to changes in resting-state activity that can be misinterpreted as primary cognitive or disease-related effects. In this paper, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 99 publications
2
38
0
Order By: Relevance
“…Temporal variation in spontaneous fMRI signals and connectivity have also been found to be altered in neuropsychiatric disorders as well as in aging ( Yang et al, 2014 ; Nomi et al, 2017 ; Calhoun et al, 2014 ). However, relatively few fMRI studies have examined the specific role of dynamically fluctuating arousal states in shaping ongoing neural or behavioral variability ( Dinstein et al, 2015 ; Liu and Falahpour, 2020 ). One barrier stems from practical challenges linked with gathering established measures of arousal (such as pupillometry and EEG) during routine fMRI scans – including the need for additional setup time, MRI-compatible hardware, and post-processing for removal of MR-related artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal variation in spontaneous fMRI signals and connectivity have also been found to be altered in neuropsychiatric disorders as well as in aging ( Yang et al, 2014 ; Nomi et al, 2017 ; Calhoun et al, 2014 ). However, relatively few fMRI studies have examined the specific role of dynamically fluctuating arousal states in shaping ongoing neural or behavioral variability ( Dinstein et al, 2015 ; Liu and Falahpour, 2020 ). One barrier stems from practical challenges linked with gathering established measures of arousal (such as pupillometry and EEG) during routine fMRI scans – including the need for additional setup time, MRI-compatible hardware, and post-processing for removal of MR-related artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Such concurrent acquisitions are not common practice in resting-state research, and the effects of fluctuations in wakefulness (or subject’s lack of compliance with keeping eyes open) are often ignored. Prior research has demonstrated that subjects have a propensity to fall asleep during resting-state scans (Allen et al, 2014; Tagliazucchi and Laufs, 2014), and that fluctuations in vigilance are to be expected (Chang et al, 2016; Liu and Falahpour, 2020). It is important to find ways to determine the occurrence of these events when no concurrent measures are available.…”
Section: Introductionmentioning
confidence: 99%
“…Although substantial variations in functional connectivity can occur on short time scales (i.e. minutes to hours) due to factors such as temporal fluctuations in subject arousal and vigilance (8, 9), our results indicate that high performance can be obtained over a 1-day interval even in the presence of these factors. Future large-scale studies with a greater time interval between training and test data will be needed to assess whether high identification accuracy can be obtained over longer intervals (i.e.…”
Section: Discussionmentioning
confidence: 62%